PEDAGOGICAL CONDITIONS OF COMMUNICATIVE COMPETENCE DEVELOPMENT OF FUTURE TEACHERS OF ENGINEERING DISCIPLINES - Zelenin , G. (Problems of Engineer-Pedagogical Education, 2021)
The article attempts to concretize the concept of «communicative competence» of future teachers of engineering disciplines as dynamic integrative professionally-important personal quality, providing the productive intercultural professional interaction in solving engineering and pedagogical problems and communication situations in the process of pedagogical activity, and including the motivationally-valuable, cognitive, activity, reflexive and evaluative components ; to substantiate and develop the pedagogical conditions for formation of communicative competence. The author of the article emphasizes that the communicative competence development of future teachers of engineering disciplines will be effective under the following pedagogical conditions: the enrichment of training content with material, updating the value of interpersonal and intercultural professional communication, which is reflected in the expansion of the content by providing the intellectual development of the students and the development of metacapabilities, metaknowledge, professional and personal qualities through the implementation of the principles of thematic interdisciplinary integration, diversity, multifunctionality and dynamism; substantive and continuous updating of the communicative educational environment as a cooperative product and as a process of communicative interaction, based on the systematic integration of human and professional contexts; activation of student activities in the communicative educational environment by student-centered pedagogical technologies using the pedagogical support of students. The article identifies the need to use the principle of thematic interdisciplinary integration as a way of pedagogical conditions realization, providing the communicative competence development, in which the ability to work well as part of a team, cooperation and social adaptation skills are developed and formed, significant for communicative competence. The author proposes a way to implement the principle of thematic interdisciplinary integration in the form of project methods, web projects, and portfolio as effective ways to create a meaningful, professional, creative/research product, which contributes to the communication skills intensification of future teachers of engineering disciplines.